Implementation of the Mental Capacity Act: a national observational study comparing resultant trends in place of death for older heart failure decedents with or without comorbid dementia - James M. Beattie; Irene J. Higginson; Theresa A. McDonagh; Wei Gao (BMC Medicine, 2022)
Abstract Background Heart failure (HF) is increasingly prevalent in the growing elderly population and commonly associated with cognitive impairment. We compared trends in place of death (PoD) of HF patients with/without comorbid dementia around the implementation period of the Mental Capacity Act (MCA) in October 2007, this legislation supporting patient-centred decision making for those with reduced agency. Methods Analyses of death certification data for England between January 2001 and December 2018, describing the PoD and sociodemographic characteristics of all people ≥ 65 years registered with HF as the underlying cause of death, with/without a mention of comorbid dementia. We used modified Poisson regression with robust error variance to determine the prevalence ratio (PR) of the outcome in dying at home, in care homes or hospices compared to dying in hospital. Covariates included year of death, age, gender, marital status, comorbidity burden, index of multiple deprivation and urban/rural settings. Results One hundred twenty thousand sixty-eight HF-related death records were included of which 8199 mentioned dementia as a contributory cause. The overall prevalence proportion of dementia was 6.8%, the trend significantly increasing from 5.6 to 8.0% pre- and post-MCA (Cochran-Armitage trend test p < 0.0001). Dementia was coded as unspecified (78.2%), Alzheimer’s disease (13.5%) and vascular (8.3%). Demented decedents were commonly older, female, and with more comorbidities. Pre-MCA, PoD for non-demented HF patients was hospital 68.2%, care homes 20.2% and 10.7% dying at home. Corresponding figures for those with comorbid dementia were 47.6%, 48.0% and 4.2%, respectively. Following MCA enforcement, PoD for those without dementia shifted from hospital to home, 62.5% and 17.2%, respectively; PR: 1.026 [95%CI: 1.024–1.029]. While home deaths also rose to 10.0% for those with dementia, with hospital deaths increasing to 50.4%, this trend was insignificant, PR: 1.001 [0.988–1.015]. Care home deaths reduced for all, with/without dementia, PR: 0.959 [0.949–0.969] and PR: 0.996 [0.993–0.998], respectively. Hospice as PoD was rare for both groups with no appreciable change over the study period. Conclusions Our analyses suggest the MCA did not materially affect the PoD of HF decedents with comorbid dementia, likely reflecting difficulties implementing this legislation in real-life clinical practice.